2010
DOI: 10.1007/s00442-010-1698-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial refuges and associational defenses promote harmful blooms of the alga Caulerpa sertularioides onto coral reefs

Abstract: Extreme population fluctuations, or outbreaks, are driven by interacting processes that are often more complex than isolated changes in consumer or resource control. Blooms of the macroalga Caulerpa sertularioides in the eastern tropical Pacific overgrew and killed reef-building corals, with blooms onto reefs corresponding to cool La Niña phases of inter-decadal fluctuations of the El Niño-Southern Oscillation. We quantified factors responsible for the maintenance of C. sertularioides patches in off-reef areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
0
21
2
Order By: Relevance
“…This contrasts with Aquat Ecol (2013) 47:433-440 437 recent studies that have shown natural abundances of epiphytic cyanobacteria can have strong negative effects on herbivory rates, and, by providing an associational refuge from herbivory, contributed to the persistence of blooms of Acanthophora spicifera (Fong et al 2006) and Caulerpa sertularioides (Smith et al 2010) on coral reefs of the Eastern Tropical Pacific. In these studies, neither A. spicifera, a highly palatable macroalga (Hay 1984;Boyer et al 2004), nor C. sertularioides, a chemically defended alga (Erickson et al 2006), could maintain populations on reefs without protection by epiphytic cyanobacteria.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…This contrasts with Aquat Ecol (2013) 47:433-440 437 recent studies that have shown natural abundances of epiphytic cyanobacteria can have strong negative effects on herbivory rates, and, by providing an associational refuge from herbivory, contributed to the persistence of blooms of Acanthophora spicifera (Fong et al 2006) and Caulerpa sertularioides (Smith et al 2010) on coral reefs of the Eastern Tropical Pacific. In these studies, neither A. spicifera, a highly palatable macroalga (Hay 1984;Boyer et al 2004), nor C. sertularioides, a chemically defended alga (Erickson et al 2006), could maintain populations on reefs without protection by epiphytic cyanobacteria.…”
Section: Discussioncontrasting
confidence: 57%
“…We predicted that cyanobacterial epiphytes would reduce herbivory rates on Halimeda, though we expected this benefit to be modest compared to that afforded more palatable species (Fong et al 2006;Smith et al 2010). Further, we predicted that the presence of cyanobacterial epiphytes would decrease net growth rates of both species of Halimeda due to competition for light or nutrients.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations